IMPLEMENTASI MIT APP INVENTOR DALAM GAME MENGENAL HURUF BERBASIS ANDROID - Iin Marliana; Ahmad Ikhwan; Teuku Muhammad Fawaati (Universitas Teknokrat Indonesia, 2023)
A game or game is something that can be played by having rules so that there is a winning and losing result, usually the game is a context that is not serious or for self-entertainment. Learning to recognize letters is one of the most important milestones in a child's development because it is the first step in learning to read and write. The game was made using the MIT App Inventor so that this game can be used on cellphones or smartphones, with the aim of this educational game not only for mere entertainment but with games we can also learn, so with educational games like this we can increase interest in learning. From the results obtained the conclusion is that this application can help respondents to learn to recognize letters. Based on the results of the recapitulation of the 5 test criteria that have been carried out, the results show that the number of answers from the respondents has a value of 100% according to the system functionality test using black box testing.